Estimation of nitrogen flow within a villagefarm model in Fakara region in Niger, Sahelian zone of West Africa - Hayashi, K.; Matsumoto, N.; Hayashi, E.; Abdoulaye, Tahirou; Shinjo, H.; Tabo, Ramadjita; Matsunaga, R.; Tobita, S. (Springer, 2012)
To determine the efficiency of utilization of organic matter in agricultural production, nitrogen flow was estimated within a village-farm model in the west of Niger, West Africa. Nitrogen was focused on in this study as it is known to be a major nutrient component of organic matter and one of the limiting nutrients in Sahelian soil. Local practices regarding the use of organic matter and pertinent information on traditional practices for soil fertility management were determined by interviews with local farmers. To estimate nitrogen flow in farmlands and consumption in the village through various activities, quantitative measurements of crop yield and organic amendment were carried out. Data on human and livestock excreta were taken from published reports. The size and classification of farmlands were as follows: 0.5 ha adjacent farmland, 1.6 ha threshing farmland, 6.0 ha transported-manure farmland, 5.5 ha corralling farmland, and 86.5 ha extensively managed farmland (EMF). Levels of nitrogen flow from these farmlands to the studied villages were 0.9, 2.9, 9.6, 15.2, and 94.2 Mg, while the flows to these farmlands were 14.6, 6.3, 13.7, 17.5, and 26.3 Mg, respectively. Upon calculation of nitrogen balance −8 kg ha−1 year−1 was estimated in EMF, but there was a positive balance in other types of farmland, which ranged from 4 to 262 kg ha−1 year−1, indicating inefficient use of nitrogen in the study area for crop production. The results indicated that nutrient flow in the study site was unequally distributed and nitrogen was not recycled. Therefore, efforts should be made to establish efficient utilization of available nutrients by reducing the loss from livestock feed and human consumption. At the same time, more research is needed to improve the management of EMF.